French Enlightened influences on Spanish anti-Franquist literature: the case of Satanael (1966) by Salvador de Madariaga (Ogigia. Revista Electrónica de Estudios Hispánicos, 2023)
The last and fifth novel in the "Esquiveles y Manriques" series, Satanael (1966), written by Salvador de Madariaga y Rojo (La Coruña, 1886-Locarno, 1978), is set in Venezuela during the 18th century, as well as in other places such as Jamaica and Cuba. The assumptions of the French Revolution, which were reviled on several occasions by Franco's ideology, contain positive connotations and deal with the message of equality to primitive Christianity. Two of the most renowned thinkers of the revolution, Russó (sic) and Volter (sic) coexist in the troubled and dichotomous mind of the protagonist, Juan Santiago Esquivel. This paper is focused on returning to Madariaga as an ideological writer, whose novels do not escape from his Europeanist and anti-Franquist vision. In fact, he considers the history of French liberal thought to be the basis of the novel we will analyse here.
Keywords: Satanael; Salvador de Madariaga; Voltaire; Rousseau; Franquism